What have Eastern Kalahari Khoe Languages lost – linguistically? - Chebanne, Andy (Stellenbosch Papers in Linguistics Plus)
Eastern Kalahari languages are spoken in the eastern parts of Botswana along the eastern fringes of the Kalahari Desert. These languages are closely related to the well-known and documented languages Gǀui and Gǁana which are spoken in the west. From a historical linguistic perspective, Eastern Kalahari Khoe languages form a dialectal continuum within themselves and within Gǀui and Gǁana. In this continuum, several features in the domains of phonetics/phonology and morpho-syntax are reduced from west to east. Clicks are missing or modified in some cognates, and this variation is observed from the western dialects to the eastern ones: (i) nǂɂũũ (western) → niũũ (eastern) ‘eat’ gǃãĩ (western) → gãĩ (eastern) ‘ibex’ Morpho-syntactically, the presence of person-gender-number markers (PGNs) varies from the western dialects to the eastern ones: (ii) Kie kwa aba sa mũũ 1SG PROG. dog PGN-fem. see ‘I see a dog’ (female) [western] (iii) Cie kwa apa mũũ 1SG PROG. dog see ‘I see a dog’ (gender unspecified) [eastern] Some phonetic or phonological features, such as delayed aspiration, are modified while others are introduced, such as tonal depression. This paper will examine click loss, PGN attrition and other syntactic features and variations within this zone. Systematic comparisons of these linguistic features will be presented and appropriate analyses of processes discussed with a view to account for the (non-)occurrences of these features in this dialectal continuum. While language contact phenomena may precipitate some of these feature losses, it is the thesis of the paper that there is an apparent regularity in some of these morpho-syntactic variations. The ultimate aim of this paper is to answer the question, “What have these languages lost linguistically?”